Apakah Faktor Demografi Mempengaruhi Minat Investor Lokal pada Pasar Modal Internasional? Analisis yang Dimoderasi oleh Literasi Keuangan - Angelina, Winna; Budiman, Johny; Hesniati, Hesniati (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The rapid growth of investment activities in national and international capital markets has significantly increased the number of investors competing for financial stability. Each investor has different investment decision-making preferences, influenced by various internal and external factors. This study focuses on internal factors in the form of demographic characteristics of local investors, such as gender, risk tolerance, religiosity, and income, complemented by financial literacy as a moderating variable. The purpose of this study is to evaluate the extent to which these factors can influence investment decision-making in international capital markets, which tend to be more complex. The research data was collected by distributing questionnaires to 280 respondents who are active investors in the Indonesian capital markets. Using the PLS-SEM analysis method, the results show that gender, risk tolerance, income, and financial literacy have a significant positive influence on investment decisions in international capital markets. Additionally, religiosity also has a positive but insignificant influence. Financial literacy as a moderating variable also tends to have a dominant negative and insignificant effect in strengthening the relationship between variables.